2018
DOI: 10.15654/tpk-170833
|View full text |Cite
|
Sign up to set email alerts
|

Effekt eines Insektenprotein-basierten Futters auf die Symptomatik von futtermittelallergischen Hunden

Abstract: Zusammenfassung Gegenstand und Ziel: Essbare Insekten (wie Mehlwürmer, Heuschrecken und Grillen) enthalten hohe Mengen an Energie, Protein, essenziellen Fettsäuren sowie Mengen- und Spurenelementen und stellen eine qualitativ hochwertige Nahrungsquelle dar. Sie sind als neuartige Proteinquellen für Futtermittelallergiker interessant und können auch in ökologischer und ethischer Hinsicht sinnvoll sein. Ziel dieser Fallserie war, die Wirkung eines neuen kommerziell erhältlichen Insektenprotein-basierte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Venison was chosen as the primary protein source for this trial since it is one of the protein sources usually incorporated in commercial foods for dogs which show adverse food reactions; similarly, insect meal showed a similar potential (7). Nevertheless, venison meal is more expensive than other common sources of proteins as well as insect meal so far and, for these reasons, was deemed eligible for the comparison of the diets.…”
Section: Diets and Digestibility Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Venison was chosen as the primary protein source for this trial since it is one of the protein sources usually incorporated in commercial foods for dogs which show adverse food reactions; similarly, insect meal showed a similar potential (7). Nevertheless, venison meal is more expensive than other common sources of proteins as well as insect meal so far and, for these reasons, was deemed eligible for the comparison of the diets.…”
Section: Diets and Digestibility Protocolmentioning
confidence: 99%
“…As pointed out by Böhm et al (7), insects may constitute an appropriate novel protein source for dogs, presenting cutaneous adverse food reactions. Nevertheless, societal negative opinions about the use of insect meal in pet nutrition have arisen, especially due to insect phobia and concerns about safety.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies investigated digestibility and immunological parameters in dogs fed on insect-based diet and no adverse effects were found [21,22]. A field study showed that insect proteinbased diets can be suggested as an alternative novel protein source for dogs with food intolerances [23]. To our knowledge, this is the first in vitro study trying to establish the link between cross-reactivity of Tenebrio molitor proteins with serum IgEs directed to storage mites in dogs with clinical symptoms of allergy.…”
Section: Discussionmentioning
confidence: 95%
“…For example, some dogs with a food intolerance to chicken protein will still react to hydrolyzed chicken liver, depending on the strength and type of the immune response. Therefore, for dogs with food allergies, it is worth introducing insect pet food into their diet [ 95 ].…”
Section: Nutritional Valuementioning
confidence: 99%
“…Studies [ 95 ] have shown that the use of domestic cricket or mulberry silkworm pupae can successfully replace poultry meal in the diet of dogs while not showing a negative effect on hematology or blood chemistry. As shown by Klinger et al [ 95 ], insects may be a new source of food for patients with adverse food reactions.…”
Section: Digestibilitymentioning
confidence: 99%